The Satyricon as Novel: the Menippean satire and the New Papyrus Discoveries (Circe de clásicos y modernos, 2018)
One of the main difficulties raised by Petronius’ Satyricon for literary criticism is its genre categorization. The objective of this paper is to demonstrate the importance of the new papyrus discoveries for this subject, especially, to consider if the relationship between the Petronian text and the Menippean Satire is a valid one, and to support the appropriateness of the label novel as a genre which describes how the Satyricon works; it will be necessary to review briefly some of the hypotheses of generic attribution of the Satyricon and some of its outstanding formal characteristics, i.e. the prosimetrum.
Keywords: Satyricon; novel; Menippean satire; prosimetrum; Iolaus